Teachers' concerns regarding the implementation of school-based assessment / Nur Haiyu Ishak - Ishak, Nur Haiyu (2014)
School-based assessment (SBA) is currently being implemented in Malaysian education system as part of its educational reform (Examination Syndicate of Malaysia, 2011).However, we know little about the concerns of the teachers as the main implementers of the transformation. Therefore the main aim of this study was to explore English language teachers' concerns regarding the implementation of school-based assessment (SBA) in Malaysia. A Stages of Concerns (SoC) Questionnaire adapted from Cheung, Hattie & Ng (2001) consisting 22-item statements was distributed to 48 secondary school teachers in Kota Bharu, Kelantan. Semi-structured interviews were also conducted with five randomly selected teachers to obtain more insights on the challenges faced by teachers and the support they needed for the effective implementation of SBA. The findings of this study revealed that a majority of the English language teachers is concerned about the informational-personal stage of SBA implementation. In other words, they were interested to learn more about SBA and how it is different and better from the previous approach. They also wanted to know how their roles would change as they implement SBA in their classrooms and how much time and energy are required in the course of this educational transformation. However, the findings also showed that there was no significant difference in terms of teachers' concerns between optionist and non-optionist, male and female, and novice and experienced ESL teachers except for the awareness stage between optionist and non-optionist English language teachers. According to the English language optionist teachers, this was mostly because they were occupied with other things than SBA and did not have much knowledge about SBA; whereas for the non-optionist English language teachers felt this was because they were rather concerned about SBA but were not keen to learn about it yet. In addition, the findings identified six main challenges faced by the teachers. They are in terms of time constraint, limited access to teaching and assessment materials to administer SBA in the classroom, reliability and validity issues in SBA implementation, coping with external pressure on the implementation of SBA, and finally, management and documentation procedures related to SBA. Last but not least, this study also identified the kind of support the teachers need. The teachers articulated that they required appropriate teaching modules,on-going training, external moderation of scores, a more teacher-friendly and realistic filing and documentation procedures, and finally they expressed a call for the stakeholders to play bigger and more effective roles during this reform. Henceforth, the results of this study will be of useful reference to concerned parties to make further improvements for the effective implementation of school-based assessment in Malaysia.